Qualitative attributes of some mango cultivars fruits - Modesto, Joyce Helena [UNESP]; Sarita Leonel, [UNESP]; Segantini, Daniela Mota [UNESP]; Souza, Jackson Mirellys Azêvedo [UNESP]; Ferraz, Rafael Augusto [UNESP] (Southern Cross Publishing, 2016)
The aim of this study was to physically and chemically characterize the fruit quality of some mango cultivars grown in a subtropical climate region of São Paulo, in the municipality of São Manuel. The experiment design was totally randomized, consisting of 4 treatments (Palmer, Parwin, Tommy Atkins and Haden cultivars) and 4 repetitions for the physical analyses and 6 repetitions for the chemical analyses. Each repetition composed of 5 fruit from each cultivar. Fruits from two production years: 2011/2012 and 2012/2013 were used for the study. According to the results we concluded that all of the cultivars are suitable for industrialization. Fruit from the Palmer and Parwin cultivars are interesting, in terms of harvesting and transporting as they showed the best values for firmness. The fruits of the Palmer cultivar presented higher physical and chemical quality.
Keywords: Analyses; Mangifera indica L.; Polyphenols; Pulp yield; Vitamin C